Tributary Medicine System of the Qing Dynasty: A Preliminary Study - Zi-Long Zhang; Yi-Sha Xian; Xiao-Jie Shi; Xue-Qi Wang; Ling-Yi Sun; Lin Su (Chinese Medicine and Culture)
Abstract. Medicine was one of the articles of tribute paid by other countries and kingdoms to the imperial court of the Qing dynasty (1644–1912). The act of paying tributes and the rituals associated with it enhanced communication and helped establish relationships between ancient China and other nations or territories. The imperial court was generous in return, which attracted many countries to pay tributes. This paper analyzes how medicines as tributes played an important role in consolidating the dominant status of ancient China, and in promoting the exchange of knowledge between Chinese and Western medicine.